Stroma AReactive Invasion Front Areas (SARIFA) – a new prognostic biomarker in gastric cancer related to tumor‐promoting adipocytes. Issue 1 (22nd October 2021) - Grosser, Bianca; Glückstein, Marie‐Isabelle; Dhillon, Christine; Schiele, Stefan; Dintner, Sebastian; VanSchoiack, Alison; Kroeppler, David; Martin, Benedikt; Probst, Andreas; Vlasenko, Dmytro; Schenkirsch, Gerhard; Märkl, Bruno
Abstract: Compared to other malignancies, there is a lack of easy‐to‐evaluate biomarkers for gastric cancer, which is associated with an adverse clinical outcome in many cases. Here, we present S troma AR eactive I nvasion F ront A reas (SARIFA) as a new histological prognostic marker. We defined SARIFA as the direct contact between a cluster of tumor glands/cells comprising at least five tumor cells and inconspicuous surrounding adipose tissue at the invasion front. A total of 480 adenocarcinomas of the stomach and the gastroesophageal junction from two different collections were classified according to SARIFA. To understand the potential underlying mechanisms, a transcriptome analysis was conducted using digital spatial profiling (DSP). It was found that 20% of the tumors were SARIFA‐positive. Kappa values between the three pathologists were good in both collections: 0.74 and 0.78. Patients who presented SARIFA‐positive tumors had a significantly lower overall survival in Collections A (median: 20.0 versus 44.0 months; p = 0.014, n = 160) and B (median: 15.0 versus 41.0 months; p < 0.0001, n = 320). SARIFA positivity emerged as a negative independent prognostic factor for overall survival (HR 1.638, 95% CI 1.153–2.326, p = 0.006). Using DSP, the most upregulated genes in SARIFA‐positive cases were those associated with triglyceride catabolism and endogenous sterols. COL15A1, FABP2, and FABP4 were differentially expressed in positive cases. At the protein level, the expression of proteins related to lipid metabolism was confirmed. SARIFA combines low inter‐observer variability, minimal effort, and high prognostic relevance, and is therefore an extremely promising biomarker related to tumor‐promoting adipocytes in gastric cancer. © 2021 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.